2005
DOI: 10.1007/s00125-005-1963-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of TV viewing and physical activity with the metabolic syndrome in Australian adults

Abstract: Aims/hypothesis: We analysed a sample of Australian adults to determine the strength of associations of TV viewing and participation in physical activity with the metabolic syndrome. Methods: This population-based cross-sectional study included 6,241 adults aged ≥35 years who were free from diagnosed diabetes mellitus and selfreported ischaemic disease and were not taking lipid-lowering or antihypertensive drugs. The metabolic syndrome was defined according to the 1999 World Health Organization criteria. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
317
9
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(373 citation statements)
references
References 30 publications
35
317
9
12
Order By: Relevance
“…Several recent studies have reported the relationship between TV viewing and excess body weight to be independent of physical activity (21)(22)(23)(24)(25) . However, in previous studies, time sitting spent in classrooms and studying at home have not been taken into consideration.…”
mentioning
confidence: 99%
“…Several recent studies have reported the relationship between TV viewing and excess body weight to be independent of physical activity (21)(22)(23)(24)(25) . However, in previous studies, time sitting spent in classrooms and studying at home have not been taken into consideration.…”
mentioning
confidence: 99%
“…Sabese que esse hábito é um importante indicador de inatividade física 25 , agravando ainda mais o problema o fato de que 57,8% do total de propagandas relacionadas a produtos alimentícios referem-se a açúcares, gorduras e doces, não sendo observados anúncios relacionados a frutas, legumes e verduras 26 . Dustan et al 27 mostraram que o hábito de assistir a mais de 14 horas de televisão por semana associou-se a um maior risco de resistência a insulina, obesidade e dislipidemia, ao passo que os indivíduos que realizavam atividade física por, no mínimo, 2,5 horas por semana apresentaram menor prevalência de resistência a insulina e dislipidemia, para ambos os sexos, e menor prevalência de obesidade e hipertensão para as mulheres. Fernandes et al 25 mostraram que adultos, com 30 ou mais anos de idade, apresentaram menor IMC quando praticavam atividade física regularmente, observando-se o contrário para as mulheres que tinham hábito de assistir à televisão, o que esteve associado com a pré-obesidade.…”
Section: Resultsunclassified
“…Siendo esto asociado tanto a anormalidades en el metabolismo de la glucosa 31,32 , como al síndrome metabólico 33 , afectando especialmente a las personas que ven más de 4 h de televisión al día. Asimismo, esta conducta ha sido relacionada con un aumento importante en el riesgo de muerte por enfermedad cardiovascular, diabetes tipo II, mortalidad por todas las causas, cáncer, etc.…”
Section: Relación Entre Conducta Sedentaria Y Actividad Físicaunclassified
“…Durante los últimos años, los estudios han mejorado significativamente la calidad de las investigaciones en esta área 39 , empleando la acelerometría [31][32][33][34]36,37,39,[40][41][42][43] , un método objetivo para cuantificar los niveles e intensidad de la actividad física, dejando de manifiesto las limitaciones inherentes al uso de los cuestionarios para dicha valoración 39,44 .…”
Section: Relación Entre Conducta Sedentaria Y Actividad Físicaunclassified